Metal/Semiconductor and Transparent Conductor/Semiconductor Heterojunctions in High Efficient Photoelectric Devices: Progress and Features - M. Melvin David Kumar; Ju-Hyung Yun; Joondong Kim (International Journal of Photoenergy)
Metal/semiconductor and transparent conductive oxide (TCO)/semiconductor heterojunctions have emerged as an effective modality in the fabrication of photoelectric devices. This review is following a recent shift toward the engineering of TCO layers and structured Si substrates, incorporating metal nanoparticles for the development of next-generation photoelectric devices. Beneficial progress which helps to increase the efficiency and reduce the cost, has been sequenced based on efficient technologies involved in making novel substrates, TCO layers, and electrodes. The electrical and optical properties of indium tin oxide (ITO) and aluminum doped zinc oxide (AZO) thin films can be enhanced by structuring the surface of TCO layers. The TCO layers embedded with Ag nanoparticles are used to enhance the plasmonic light trapping effect in order to increase the energy harvesting nature of photoelectric devices. Si nanopillar structures which are fabricated by photolithography-free technique are used to increase light-active surface region. The importance of the structure and area of front electrodes and the effect of temperature at the junction are the value added discussions in this review.